PENGARUH EKONOMI MASYARAKAT PESISIR MELALUI DEVERSIFIKASI PRODUK KERUPUK UDANG DI DESA PUNTI SOROMANDI: Economic Influence Of Coastal Communities Through Shrimp Cracker Product Deversification In Punti Soromandi Village - Putri, Nurul; Maulana, Agus; Raodah, Raodah; Iklimah, Nur; Yusari, Yusnia; Annisah, Annisah; Mahyudin, Mahyudin; Fadhillah, Adyatma; Hayril, Hayril; Wahyuramadhan, Wahyuramadhan; Amirulmukminin, Amirulmukminin; Kusumayadi, Firmansyah (Yayasan Al-Amin Qalbu, 2025)
This study aims to improve the coastal community's economy through the diversification of shrimp cracker products in Punti Village, Soromandi District, Bima Regency. The method used is a participatory approach involving training, assistance, and product innovation. The results of the activities show that product diversification—such as spicy shrimp crackers, mini shrimp crackers, and premium-packaged shrimp crackers—can increase both market value and market reach. The community has begun to demonstrate independence in production and marketing. Through a collaborative and innovative approach, product diversification has proven effective as a strategy for strengthening the local economy